Odpowiedź :
Odpowiedź:
2 * log_ ½ 5 + log_ ½ 0,01 = log_½ 5² + log_½ 0,01 = log _½ 25 + lig_½ 0,01 = log_½(25 * 0,01) = log_½ 0,25 = log _½ ¼ = 2
Wykorzystane własności logarytmów:
n * log _b a = log _ b a^n
log_a b + log_a c = log_a (b * c)
log _ a c = b <=> a^b = c
2 * log_ ½ 5 + log_ ½ 0,01 = log_½ 5² + log_½ 0,01 = log _½ 25 + lig_½ 0,01 = log_½(25 * 0,01) = log_½ 0,25 = log _½ ¼ = 2
Wykorzystane własności logarytmów:
n * log _b a = log _ b a^n
log_a b + log_a c = log_a (b * c)
log _ a c = b <=> a^b = c
Odpowiedź:
[tex]2log_{\frac{1}{2} }5+log_{\frac{1}{2} }0,01=?[/tex]
[tex]2log_{\frac{1}{2} }5=log_{\frac{1}{2} }5^2\\[/tex]
[tex]log_{\frac{1}{2} }5^2+log_{\frac{1}{2} }0,01= log_{\frac{1}{2} }25+log_{\frac{1}{2} }\frac{1}{100}[/tex]
Skorzystajmy z pewnej zależności:
[tex]log_{a} x+log_{a} y=log_{a}(x*y)[/tex]
[tex]log_{\frac{1}{2} }25+log_{\frac{1}{2} }\frac{1}{100} =log_{\frac{1}{2} }(25*\frac{1}{100})=log_{\frac{1}{2} }\frac{25}{100}=log_{\frac{1}{2} }\frac{1}{4}[/tex]
[tex]\frac{1}{2}^x =\frac{1}{4}\\\\[/tex]
dla x=2
[tex]\frac{1}{2} ^2=\frac{1}{4}[/tex]
Odpowiedź: 2
Szczegółowe wyjaśnienie: